IDENTIFIKASI PENERAPAN CONTINUOUS IMPROVEMENT UNTUK MENDUKUNG WORK LIFE BALANCE PADA DIVISI KEUANGAN OPERASIONAL PT HM SAMPOERNA TBK - Febriany Sabella; Senny Harindahyani (CALYPTRA, 2018)
Continuous improvement is one of managerial accounting concept that is focused on increasing quality by reducing waste through effeciency and effectiveness. Continuous improvement is set by company as a principle to sustained a competitive advantage by implementing continous improvement as a company's core principle. PT HM Sampoerna Tbk is one of the company that implement continous improvement as company's core principle. Sampoerna continuously improve for their “Three Hands Phylosophy” that's for adult smokers, employee and business partners, and society at large. Specifically for their employees that's believed as company's key of success, Sampoerna give their employees a feedback by continuously make a program to success work-life balance. Work-life balance is defined as a situation in which workers feel that they are capable on balancing their works and non-work commitments. With the complexities and higher mobility in MNC, work-life balance considers as one of workers challenge nowadays.